Environmental Pollution in five floors (5th to 9th) Resulting From the use of Depleted Uranium Weaponry in the AL-Tahreer Tower Building - Nabeel hashim Ameen; Mazen Abbas Al-ghirrawy; Hamza Hadi Kadhim (Journal of Madenat Alelem University College, 2014)
The goals of this study include measuring the increase in radioactivity and removal the contamination regions to protect the population and the environment resulting from bombing the AL-Tahreer Tower Building (the Turkish restaurant previously) by the depleted uranium bullets through direct measurement and sampling of soil from five floors (5th,6th,7th,8th,and 9th) of the building, which contains fourteen floors in addition to basement by using different types of portable monitoring equipments. The results of radiological surveys by using the portable monitor (CAB) indicated the presence of contaminated soil reached to 55 c/sec, and small particles of depleted uranium shells has very high levels of contamination reached to 70 c /sec ,while the background level is (0.5c/sec) ,and the higher exposure rates is 55 µR/hr when the portable monitor (Ludlum) put on the contaminated regions approximately on distance 0.5 cm), where the natural background level is 9 µR/hr in the floors of the building. The radiological analyses of the collected soil samples were done in the laboratory of the center of Radiological Researches in the Ministry of sciences and Technology by using gamma spectrometry (which contains High- purity Germanium Detector) with a efficiency of 40% and resolution 2 keV for Energy, 1.33Mev, collection, preparations and tests of soil samples were all done according to IAEA.The laboratory results indicated the presence of high concentrations of the isotopes Th-234 (1550.1) Bq/kg, and Pa-234m (1394.8) in the soil samples taken from the floors while the concentrations of Th-234 and Pa-234m in natural background levels are (nearly 40, nil) Bq/Kg respectively which is a clear indication of the presence of high concentrations an isotope of uranium - 238 as they are supposed to be in equilibrium radiation.